The Hydrodynamic Coefficient Analysis and Motion Control of the Lingyun Moveable Lander. (7th October 2021) - Li, Guoxin; Zhang, Shaowei
Abstract : A moveable lander has the advantages of low cost and strong controllability and is gradually becoming an effective autonomous ocean observation platform. In this study, the hydrodynamic property of the Lingyun moveable lander, which has completed experiments in the Mariana Trench in 2020, is analyzed with the semiempirical method and computational fluid dynamic (CFD) method. We calculate the inertial hydrodynamic coefficients and viscous hydrodynamic coefficients of the lander. The results show that the CFD can provide the hydrodynamic property for the moveable lander's design. The dynamic equations and kinematic equations are completely constructed combined with the hydrodynamic coefficients. Subsequently, this paper utilized the PID control method and S control method to control the motions of the lander. The simulation results show that the methods accurately follow the preplanned path.